1998
DOI: 10.1137/s0036139996302252
|View full text |Cite
|
Sign up to set email alerts
|

A Class of Low-Frequency Modes in Laterally Homogeneous Fluid-Solid Media

Abstract: By a fundamental wave mode in a laterally homogeneous fluid-solid medium, we mean a propagating mode that continues to exist as a propagating mode down to arbitrarily low frequencies. In underwater acoustics with a fluid medium having a pressure-release surface, there is no fundamental mode since each mode has a lower cutoff frequency. In plate acoustics there are two fundamental Lamb modes, a symmetric one (the quasi-longitudinal wave) and an antisymmetric one (the bending wave). There is also a fundamental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The structure for the class of low-frequency modes such that lim inf S " k( )"(R was determined in references [16,17]. It was shown that lim S k( )"q always exists for such a mode.…”
Section: The Mode Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The structure for the class of low-frequency modes such that lim inf S " k( )"(R was determined in references [16,17]. It was shown that lim S k( )"q always exists for such a mode.…”
Section: The Mode Structurementioning
confidence: 99%
“…Fluid}solid media with an arbitrary number of #uid and solid regions, and with a general variation with depth for the velocity and density parameters, were considered by Ivansson [16,17]. By an asymptotic study of the dispersion function, all normal modes for which the horizontal wavenumber tends to zero with the frequency could be determined explicitly.…”
Section: Introductionmentioning
confidence: 99%